Protocolos de remoção química de resíduos de cimento endodôntico na dentina: influência sobre formação de camada híbrida e resistência de união a sistemas adesivos - Guiotti, Flávia Angelica [UNESP] (2015)
The aim of this study was to evaluate the cleaning capacity of the dentin surface, contaminated by a endodontic sealer containing epoxy resin (AH Plus), provided by ethanol or by xylene and its effects on the interface dentin / dentin adhesive system, by evaluating the formation of the hybrid layer and the bond strength of Scotchbond Universal (3M ESPE), immediately or after 7 days of dentin cleaning and, assessing the formation of the hybrid layer and the bond strength of Adper Scotchbond Multi Purpose (3M ESPE), immediately after cleaning the dentin surface impregnated with the sealer. Besides, compare the effects of cleaning substance (95% ethanol or xylene) and the etching time with phosphoric acid at 37% (immediately or after 7 days) to obtain open dentinal tubules and to evaluate the residues persistence of a sealer-based epoxy resin (AH Plus) on the dentin surface. In Chapter 1, dentin fragments of bovine incisors were treated with root canal irrigation, impregnated with sealer and divided into 4 groups (n = 10): G1 (EIDE), ethanol 95.0% - DE immediate; G2 (XIDE), xylene - DE immediate; G3 (EPDE), ethanol 95.0% - DE after 7 days and G4 (XPDE), xylene - DE after 7 days. After obtaining the SEM pictures (500X), the open dentinal tubules counts were performed using Photoshop CS5 program. Another 40 fragments were also prepared and also obtained SEM pictures (500X) for evaluating the persistence of sealer residues in the dentin using scores. The count of open dentinal tubules was analyzed with ANOVA and Tukey tests (P = 0.05) and the persistence of residues with the Kruskal Wallis and Dunn tests (P = 0.05). The cleaning protocol with xylol and etching after 7 days provided the greatest amount of open dentinal tubules and lowest persistence of residues in the dentin (P <0.05). There were no differences between the other groups (P> 0.05). In Chapter 2...(Complete abstract electronic access below)